1982
DOI: 10.3171/jns.1982.57.4.0441
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of spinal column deformity after multilevel laminectomy in children and adults

Abstract: Fifty-eight patients, all less than 25 years of age, underwent multilevel laminectomy for conditions that in themselves do not usually cause spinal deformity. Spinal deformity developed in 46% (12 of 26) of the patients who were less than 15 years of age, but in only 6% (two of 32) of the patients aged 15 to 24 years. Spinal deformity developed in all (100%) patients who had cervical laminectomy, in 36% of those who had thoracic laminectomy, and in none (0%) of those who had lumbar laminectomy. There was no co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
176
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(183 citation statements)
references
References 15 publications
3
176
1
3
Order By: Relevance
“…19 Fig. 4 Weight mean difference of recovery rate between anterior surgery group and posterior surgery group.…”
Section: Study or Subgroupmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Fig. 4 Weight mean difference of recovery rate between anterior surgery group and posterior surgery group.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…Further, some authors have suggested that patients who undergo posterior laminoplasty or laminectomy are more prone to develop cervical kyphosis or instability than those who receive treatment via anterior approaches [19].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of chronic pain was 30% and the reported intensity was low (3/10 cm) at GRS for chronic pain. Laminectomy series usually report higher values [15,18,24,34,37]. Laminotomy offers the same exposure of laminectomy while aiming to the preservation of functionally important structures which are left untouched or at least reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…Laminectomy will effectively decompress the spinal cord, but progressive kyphotic deformity and cervical instability are common in children after laminectomy. [19][20][21] In addition, the surgical scar on the posterior neck has generally gone unnoticed because it can easily be covered with hair. If progressive neurological deterioration occurs, laminoplasty with decompression of the spinal cord should be considered in patients with calcified intervertebral disc herniation.…”
Section: Discussionmentioning
confidence: 99%